Determining Potassium Nitrate performance as solid rocket propellant for rocket engine - Dahalan, Md. Nizam; Mohd Jaafar, Mohd Nazri; Wan Ali, Wan Khairuddin; Mamat, Rizalman; Abd. Ghani, Mohd Shaiful Azman (Universiti Teknologi Malaysia, 2003)
Research and development on solid rocket propellant were carried out extensively on the whole process of production and performance testing. Solid rocket propellant was produced by using potassium nitrate as oxidiser and sucrose as organic fuel. Press- moulding method was selected to produce the propellant. Based on experiments, it was found that the compressed moulding method gives more uniform and stable propellant compared to the other method of preparation. Propellant burning rate test and static thrust test were carried out in order to determine the characteristic of solid propellant. Burning rate test was conducted on the standard strand burner test rig under atmospheric pressure. The effect of oxidizer and fuel composition on burning rate was studied. It was found that the burning rate was influenced by oxidizer-fuel (O/F) ratio. There are several characteristic parameters of solid propellant that could be found from the static thrust test. The thrust produced by the rocket motor was measured directly from static thrust test. Based on the propellant with O/F ratio of 65/35, the thrust produced was more than 300 N with total impulse of 150.04 Ns and specific impulse of 154.8 s. From experiments, it was found that the potassium nitrate based solid propellant has good characteristics and has the potential to be develop further as propulsion system for a launch vehicle.